2016
DOI: 10.53369/pvga1050
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Social-Financial Performance Link: Evidence from Pakistan

Abstract: This empirical investigation has been conducted to constitute a link between corporate social performance and corporate financial performance in Pakistani listed firms. For this purpose the data from seventy listed non-financial firms at KSE from twenty one sectors which are engaged in CSR activities for a period of six years from 2008 to 2013 was employed. The two-stage least square (TSLS) methodology has been used to explore a link between CSP and CFP. The results of study revealed that there is a simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The studies by Zulfiqar et al [68] and Ali et al [86] have used social identity theory as depicted in the Table 2 below. The studies by Majeed et al [51]; Butt and Butt [57] and…”
Section: Critical Discussion On the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The studies by Zulfiqar et al [68] and Ali et al [86] have used social identity theory as depicted in the Table 2 below. The studies by Majeed et al [51]; Butt and Butt [57] and…”
Section: Critical Discussion On the Literaturementioning
confidence: 99%
“…This may be attributed to the satisfaction of the stakeholders that pays off to the firms. On the other way around, there may be slack resources perspective as there is a worthy circle between CSR and financial performance [8,57] meaning that both these constructs pay off each other. The true check for the acceptability of the relationship between CSR and financial performance needs attention in Pakistan.…”
Section: Critical Discussion On the Literaturementioning
confidence: 99%
“…The results of their study reveal that ethical leadership influences CSR which positively affects both commercial and operational performance. Similarly, Butt et al (2016) find CSR as a significant mediator between ethical leadership and organizational performance. Still, the mediation of CSR is neglected by most of the literature on the service sector aiming to identify the relationship between ethical leadership and organizational performance.…”
Section: Corporate Social Responsibility As Mediatormentioning
confidence: 92%
“…the banking sector) and pointed out that it plays an important role in organizational commitment. Similarly, Butt et al (2016) found that ethical leadership improves organizational performance. Therefore, on the basis of this discussion, the following hypothesis is formulated: H1.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
“…A large number of formal definitions are available for the term business ethics. For example, it has been defined as the application of principles of doing the right thing, in the right way, for the right reason (Butt, 2016), and as a right or wrong behavior (Lewis, 1985). This concept of right or wrong is determined by societal norms and values (Staub, 2013).…”
Section: Introductionmentioning
confidence: 99%